Introduction - Zahorik, J.; Ylonen, A. (The Horn of Africa since 2018: Continuities, transformations, and prospects, 2025)
The Horn of Africa has undergone enormous changes and transformations in the last few years. Regime change in Ethiopia and the revolution in Sudan followed by wars in both countries have affected the whole region. However, despite these transformations and disruptions, many political aspects elsewhere in the Horn show a high level of continuity, such as Isaias Afwerki, Ismail Omar Guelleh, and Salva Kiir Mayardit rule in Eritrea, Djibouti, and South Sudan, respectively, while ethnic, clan, religious, center-periphery, and highland-lowland divisions define politics. This introduction summarizes key events in the region since 2018 and provides a brief overview of the chapters in the volume which are divided into three parts: continuities, transformations, and prospects. The international significance of the Horn of Africa will only grow in the future through more engagement and interaction with external powers.